Working Stiff : 2 Years, 262 Bodies and the Making of a Medical Examiner. - Melinek, Judy (Allen & Unwin, 2014)
An engrossing, poignant, humorous and gripping account of the life of a medical examiner - and the secrets a body can reveal. A must for fans of true crime, the best science writing, and behind-the-headlines memoirs.